Evaluation of functional activity components in the occupational therapy program for patients with stroke - Tung, Do Ngoc; Ogano, Misao; Hiroki, Shiramasa; Taniguchi, Takamichi (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
Occupational Therapy (OT) with the aim of improving Functional Activities (FAs) for patients. In theory framwork, the FAs should be the main component and take up most of OT intervention. This research's goal is to assess the ratio of the composition of FAs to different therapeutic modalities on stroke's patient by observing 31 OT sessions of 12 therapists with a lisence of 3 years experience or more on 31 stroke patients (14 acute stage, 17 recovery stage) in Japan. The result showed that the duration time for one session was with an average of 45.5 ± 11.3 minutes; of which 30% of session was used for FAs. Activities relating to cooking (8.5%) and functional mobility (7.8%) were the most frequently used activities. Three forth of the treatment time is spent on activities in the sitting and standing positions, and the remaining time is spent on activities in the lying position. At the acute stage, there is a link between the level of patients independence (FIM) and the use of FAs in the tre program (P<0.05). However, at the recovery stage, the level of independence of the patients increased significantly but did not change the composition of the FAs. This study illustrated that the therapists seem to have focused more on activities with the aim of improving body structure and function defects according to the ICF classification.